Chapter 5.25 Evolution of RMA in Slovenia - Primož Petek; Tjaša Baloh; Vanda Baloh (Emerald Publishing Limited, 2023)
This chapter outlines the research management and administration (RMA) as a profession and work field in Slovenia. Thus, we present an overview of the Slovenian research system, describing how this system has evolved over time. In addition, we explain the emerging need for RMA skills, including its self-organisation component and the challenges that lie ahead. A section is dedicated to Slovenian RMA demographics using RAAAP-2 and RAAAP-3 surveys. The conclusions of the chapter focus on a forecast for the future of RMA in Slovenia and several possible paths to follow for its community.
10.1108/978-1-80382-701-820231059; 10.1108/978-1-80382-701-820231059; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262